(untitled) (Historia, 2021)
This is an ambitious book which focuses on the period from the inter-war years to the implementation of Bantu Education in the early 1950s, although in passing it touches on the entire colonial period that dates back to the 1800s. Chisholm’s work reveals the many ways in which the unique historical beginnings of western education and the implementation of Bantu Education in South Africa were more complex and complicated than simply a racial analysis of the white colonizer conquering and socializing the African through education. In this book, Chisholm situates the mission in its broader Lutheran context and discusses differences between them over their educational politics. She further explores how power relations shifted between the mission, the state, and communities and how the mission’s influence was gradually and differentially eroded in Natal and the Transvaal. Finally, she examines the politics of continuities and changes in curricular, medium of instruction and textbooks in schools and teacher training.